Stagnasi Skema Hutan Tanaman Rakyat di Kabupaten Barru, Sulawesi Selatan: Stagnation of Community Plantation Forest in Barru Regency, South Sulawesi - S. Samad, Radhiatunnisa; Samad, Sofyan; Rusadi, Nusrah; Trianingtyas, Andhira; Hartati, Bunga Resa; Putra, Rizki Auliansyah; Putro, Dhymas Sulistyono (JURNAL HUTAN TROPIKA, 2025)
The Community Plantation Forest (CPF) program was established as a policy instrument to expand community access to forest management, support forest rehabilitation, and improve local livelihoods. However, its implementation in Barru Regency, which holds one of the largest allocations of HTR permits in South Sulawesi, has remained stagnant since the early phase of the program. This study aims to identify the factors influencing the implementation of HTR management and to examine community interest in the program. Data were collected through field observations and interviews conducted with Forest Farmer Group’s (FFGs) using a key informant sampling method. The factors affecting policy implementation were analyzed across five dimensions: policy, institutional arrangements, stakeholders, human resources, and forest resources. The findings indicate that strengthening community capacity and institutional structures, enhancing stakeholder collaboration, and implementing consistent monitoring and evaluation mechanisms are essential to improving the performance and long-term sustainability of the HTR program in Barru Regency.